METHODOLOGY OF TEACHING MILITARY SCIENCES (Web of Teachers: Inderscience Research, 2024)
The methodology of teaching military sciences is one of the important aspects of the military education system and includes methods, methods and principles aimed at the effective organization of the educational process and the development of military knowledge and skills of students. The teaching process should be aimed not only at imparting theoretical knowledge, but also at forming practical skills. This is important for improving students' readiness for military service.